Checklist and type designations of New Zealand Aleocharinae (Coleoptera: Staphylinidae) - Leschen, Richard A. B.; Newton, Alfred F. (Zootaxa, 2015)
A checklist of all identified species of the staphylinid subfamily Aleocharinae known to occur in New Zealand and associated outer islands (including the Kermadec, Chatham and Auckland Islands) is presented. Included for each species, and for synonyms known from New Zealand, is a reference to the original description, type locality and type depository, and for each species the known distribution within and outside New Zealand. Type material was sought and is summarized for all indigenous New Zealand species, with lectotypes designated for 55 names and confirmation of holotypes and prior designation of lectotypes when necessary. One nomenclatural change is implemented: the preoccupied generic name Gyronotus Cameron is replaced by Marecon Blackwelder. Other taxonomic changes are not made, pending further study and revision that is badly needed. Of the 169 currently known species of Aleocharinae reported from New Zealand, at least 26 are believed to be adventive from elsewhere, two may occur naturally elsewhere, and 141 (83%) are evidently endemic to this region. Of the 65 genera represented by these described species, 27 (42%) are also endemic to the New Zealand region; an additional five genera represented in New Zealand only by unidentified or undescribed species are also noted. Ten genera are adventive. However, the actual aleocharine fauna of New Zealand will undoubtedly be much larger, and the generic composition highly modified, when the fauna is fully explored and studied in a world context.